Structural performance of cold-formed high strength steel tubular X-Joints under brace axial compression. (1st April 2020) - Pandey, Madhup; Young, Ben
Highlights: 34 cold-formed high strength steel X-joints were tested for their static strengths. Chord face, chord side wall and combination of these two failure modes were observed. Static strengths were compared with the predictions of EC3 and CIDECT. Existing design provisions of EC3 and CIDECT are generally not accurate and reliable. Reduction factor is required for X-joints with small β values only. Abstract: The experimental investigation presented in this study focused on the static strengths and load-deformation behaviour of cold-formed high strength steel tubular X-joints made up of S900 and S960 steel grades. The X-joints include brace members made up of square, rectangular and circular hollow sections, while chord members were made up of square and rectangular hollow sections. The nominal yield strengths of square and rectangular tubular members were 900 and 960 MPa, while the nominal yield strength of circular tubular members was 900 MPa. Two configurations of tubular X-joints were fabricated, first, where both brace and chord members were made up of square and rectangular hollow sections, and second, where circular hollow section braces were welded to square and rectangular hollow section chord members. The welds were laid using semi-automatic gas metal arc welding process. A total of 34 tests was conducted where an axial compression was applied through the brace members without any chord preload. The ratio of brace-to-chord width ( β ) ranged from 0.34 to 1, brace-to-chord thickness ( τ ) from 0.53 to 1.28, chord width-to-thickness (2 γ ) from 20.2 to 38.9, and chord side wall slenderness ( h0 / t0 ) from 12.7 to 39.0. In order to assess the applicability of the existing design provisions, test strengths were compared with the nominal strengths obtained from the Eurocode 3 (EC3) and CIDECT. It is shown that the existing design provisions are not capable of providing accurate and reliable predictions for cold-formed high strength steel tubular X-joints made up of S900 and S960 steel grades.